1995
DOI: 10.1002/ijc.2910620605
|View full text |Cite
|
Sign up to set email alerts
|

Detection of an epstein‐barr‐virus variant in T‐cell‐lymphoma tissues identical to the distinct strain observed in nasopharyngeal carcinoma in the taiwanese population

Abstract: An EBV variant has been identified in NPC tissues in Taiwan. This EBV variant contains a point mutation in exon I of the LMP I gene. This mutation results in the loss of an XhoI site at nt 169,426, which is present in strain B95-8. In addition, this variant contains a 30-bp deletion in exon 3 of the gene. The recent demonstration of the prevalence of EBV-containing nasal and peripheral T-cell lymphoma in this region drove us to evaluate the presence of this NPC-EBV strain in 7 cases of T-cell lymphoma, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
60
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 15 publications
8
60
1
Order By: Relevance
“…27,29 However, none of the NPC cells tested in previous reports have expression of EBV genome or detectable residential virus after prolonged propagation in culture. 34,35 Given that EBV DNA is expressed in the majority of primary NPC biopsies and also in tumors found in Southern China, [36][37][38] results from the use of EBV (1) tumor cells and the demonstration of their responsiveness to [Au(TPP)]Cl become more clinically relevant and significant. Furthermore, our titration experiments also indicate a safety concentration window that allows [Au(TPP)]Cl to exert its cytotoxicity against tumor cells without significantly affecting the survival of PBMCs and fibroblasts (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…27,29 However, none of the NPC cells tested in previous reports have expression of EBV genome or detectable residential virus after prolonged propagation in culture. 34,35 Given that EBV DNA is expressed in the majority of primary NPC biopsies and also in tumors found in Southern China, [36][37][38] results from the use of EBV (1) tumor cells and the demonstration of their responsiveness to [Au(TPP)]Cl become more clinically relevant and significant. Furthermore, our titration experiments also indicate a safety concentration window that allows [Au(TPP)]Cl to exert its cytotoxicity against tumor cells without significantly affecting the survival of PBMCs and fibroblasts (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Most LMP1 genes derived from Chinese NPC biopsy specimens are marked by the 30-bp deletion (nt 168266 to 168295) in the carboxyl terminus, a loss of the XhoI site in the amino terminus, and multiple base substitutions in the coding region (9,10,22,25). Although the 30-bp deletion in LMP1 was detected in 100% of 48 NPC biopsy specimens in Taiwan (8), in 34 of 37 NPC biopsy specimens in Hong Kong (11), and in 16 of 21 NPC biopsy specimens in Guangxi and Shanghai (51), Zhang et al (56) reported that the 30-bp deletion in LMP1 represents a geographical-or race-associated polymorphism rather than an NPC disease phenotype-associated polymorphism. Recently, the consistent sequence variation in LMP1 has been used to distinguish the various EBV strains, which were termed strains China 1, China 2, Med, China3, Alaskan, NC, and B95.8.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of the 30-bp deletion and six point mutations of the LMP-1 gene remains unclear. The deletion strain is prevalent in Taiwan, is not restricted to nasopharyngeal carcinoma, and was also found in throat washings of healthy individuals (21). Therefore, the clinicopathologic significance of the 30-bp deletion of Exon 3 of the LMP-1 gene in FDC tumors warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%